(untitled) (Journal of Pharmaceutical Negative Results, 2022)
"AIM"- Using a new drug delivery technology, such as Nifedipine microspheres, this study sought to increase the solubility of a particular calcium channel blocker."MATERIAL & METHODS"- Quasi-emulsion diffusion is used to create floating microspheres of Nifedipine. A magnetic stirrer at 50 rpm is used at room temperature to dissolve the predetermined weighted amount of Nifedipine, ethylcellulose, "polyethylene oxide, and hydroxy propylmethyl cellulose (HPMC K15M)". Particle size, bulk density, compressibility index, and attitude of repose are used to describe the microsphere's "values beneficial in the prediction of Flowability." There has been careful pouring of the microspheres through the funnel until they are just touching the funnel's tip. "RESULTS & DISCUSSION"- The microsphere is previously arranged by removing water from the cavity of the microsphere and air drying it. In F3, F7, and F9, the percentage yield of microspheres rose with increasing ethyl cellulose concentration. The drug content was checked to ensure that the medication was uniformly placed in the microspheres during the microencapsulation method. However, mechanical factors cause the loss of the final product. Thus the procedure yield may not be 100 percent. The readings of θ varied from 25° to 29°, suggesting that the powder should have a satisfactory flow quality for the formulation. CONCLUSION- It is determined that all of the parameters for optimizing floating microspheres are found to be adequate. Evaluation of formulations' dependability under accelerated balancing situations.